Complete Stability Analysis for Delayed Economic Systems - Jun-Xiu Chen; Gao-Xia Fan; Xu Li (Mathematics)
In this paper, we will study the stability of economic systems with delay, also called delayed economic systems. We focus on the complete stability problem with respect to delay for linearized economic systems. First, we will review three types of delayed economic systems and will see that the characteristic functions are all in the form <semantics>f(λ,τ)</semantics>. Then, we will solve the complete stability problem by using the frequency-sweeping approach, which is introduced for the stability studies of economic systems (for the first time). As a consequence, the complete stability problem with delayed economic systems can be systematically solved. Finally, numerical examples will show that the whole stability set of <semantics>τ</semantics> for a delayed economic system may be determined accurately.